Design and validation of molecular diagnostic assays for key prognostic biomarkers, FLT3-ITD, NPM1, DNMT3A and CEBPA in cytogenetically normal aml patients at Tygerberg Hospital, South Africa - Losper, Kaylee Chantel (Stellenbosch : Stellenbosch University, 2025)
Thesis (MMed)--Stellenbosch University, 2025.